POST-COMMUNISM AFTER 20 YEARS: THE COMPARISON OF DEMOCRACY INDICATORS OF NORDIC COUNTRIES, SOUTHERN EUROPE AND CENTRAL AND EASTERN EUROPE - Spurga, Saulius (Politologija, 2015)
It is a common perception that 20 years after fall of communism, the countries of Central and Eastern Europe (CCEE), even though they have joined the EU, belong to the group of the post-communist countries. Post-communism is defined as the period of transition to democracy in the former communist countries after the fall of communism. This period is characterized by a significant difference in the quality of democracy between the country in transition and mature Western democracies. Yet is it correct to assert that 20 years after fall of communism the communist past constitutes the most important factor determining the status of democracy of the CCEE, which have already joined the EU? Is it correct to assert that the CCEE are still in transition? On the other hand, 20 years is quite a long time. One can ask, is it justified to call “transition” a period, which lasts so long? If the significant differences in the quality of democracy between the CCEE, the former communist countries, and the mature Western democracies persist, it would be reasonable to assert that in the CCEE democracy of a distinctive nature has been emerged. This means that there are significant differences in civilization and culture that prevail between the CCEE and mature Western democracies. When analyzing the CCEE, known Western political and economic development models could not be fully applied. This article analyses whether a clear distinction in the quality of democracy between the CCEE, which are new member states of the EU, and the old member states, could still be made. The starting point of the research has been the acceptance that the group of old member states of the EU is not homogeneous with respect to the quality of democracy. The analysis has been conducted by comparison of the democracy indicators of the CCEE (Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Slovakia, Slovenia), the countries of Southern Europe (Greece, Portugal, Spain) and the Nordic countries (Denmark, Finland, Sweden). The countries of Southern Europe and the Nordic countries are the old members of the EU. The comparison has been made in five different areas, using five sets of indicators, which are usually related to the quality of democracy: (1) the Economist Intelligence Unit’s Index of Democracy, (2) voter turnout in national and EU parliamentary elections, (3) citizen satisfaction with the way democracy works, (4) the Worldwide Governance Indicators (Voice and Accountability, Rule of Law), (5) freedom of the press. The research has revealed that scores of democracy indicators of the CCEE and the countries of Southern Europe do not differ significantly. In some cases, the scores of the group of the CCEE correspond to the better quality of democracy. The scores of the democracy indicators of individual countries of the two groups overlap in most cases. However, the analysis has exhibited a considerable difference in the scores of democracy indicators between the countries of Southern Europe and Nordic countries, although the countries of these two groups belong to the group of the old member states of the EU. Thus, the difference in the scores of democracy indicators inside the group of the old member states of the EU is bigger than the difference between the CCEE and the countries of Southern Europe. The research has found that a clear distinction in the quality of democracy between the CCEE, which are the new member states of the EU, and the old member states, does not exist. With regard to the quality of democracy, there is no reason to distinguish the CCEE as a separate group with a different civilizational and cultural nature, because the scores of the democracy indicators of the CCEE and some old member states of the EU overlap. The fast transition of the period, which is called “post-communism”, has ended, and separate states have different systems of government. The communist past is still an important factor, but only as one among many other factors, which impact on the development of the countries. The communist past is not a fatalistic imprint. Twenty years after fall of communism, the responsibility falls on the decision-making institutions of the countries. The criteria of democracy, which are applied to the countries of mature Western democracies, have to be applied to the CCEE without any exceptions.